The Quality of Buffalo Sperm Following Preservation Using Different Diluents and Sperm Concentrations - Yendraliza Yendraliza; Muhammad Ridho; Muhamad Rodiallah; Zumarni Zumarni (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
Artificial Insemination (AI) success depends on the quality of the frozen semen. The quality of the frozen semen of swamp buffalo in Indonesia is still low. The study was conducted to determine the quality of buffalo sperm following freezing using three different diluents and three different doses. The study used buffalo semen from the Tuah Sakato Artificial Insemination Center, Payakumbuh (n = 3). The semen collecting was carried out once a week for 10 weeks (replication). The research method used was 3x3 factorial randomized block design. The first factor was diluent (Triladyl®, Andromed® and Tris egg- yolk) and the second factor was the dose of spermatozoa (10 and 15 and 20 x 106 sperm/ml). Data were analyzed using variant analysis, while the differences between treatments were tested by Duncan Multiple Range Test. The results showed that the plasma membrane integrity of buffalo sperm was found in Andromed® diluent, while tris egg-yolk diluent gave better motility, viability, plasma membrane integrity and recovery rate at a sperm concentration of 20 x106 sperm/mL compared to triladyl® diluent and a sperm concentration of 10 and 15 x106 sperm/mL. It was concluded that andromed® diluent and tris egg-yolk gave better motility, viability, plasma membrane integrity and recovery rate at a sperm concentration of 20 x106 sperm/mL compared to triladyl® diluent and a sperm concentration of 10 and 15 x106 sperm/mL. of Buffalo of sperm abnormalities not sicnificantly by the type of diluent but are influenced by sperm concentration.